ANALISIS EFEKTIVITAS METODE PROBLEM BASED LEARNING DALAM MENINGKATKAN TEKNIK DRIBBLING SEPAK BOLA PADA MAHASISWA PJKR - Manalu, Nimrot; Joel Tulus; Sembiring, Feliks Kevin Benayanta; Sitorus, Muhammad Farhan; Farhan, MHD. (Universitas Negeri Medan, 2025)
Sports, particularly football, play a vital role in maintaining physical and mental fitness, as well as serving as a means to achieve achievements. One of the essential basic skills in football is dribbling, which requires good technical and physical skills. The Problem-Based Learning (PBL) model can be an effective solution in teaching dribbling skills, as it emphasizes active student involvement in solving real-life problems. This study aims to analyze the application of dribbling techniques through the PBL method in football learning for students of the Physical Education, Health, and Recreation (PJKR) Program at Universitas Negeri Medan, class of 2023. The research findings show that the application of the PBL method significantly improves students' understanding and skills in dribbling techniques, with notable progress in knowledge, skills, and attitudes. The application of this PBL model provides students with opportunities to collaborate, improve social skills, and develop critical and creative thinking abilities. This research contributes to the development of more effective and applicable sports learning models.